The Relationship Between Education Level and Environmental Awareness With the Implementation Sustainable Fishing in Gorontalo Bay - Sahi, Zulkarnain; Podungge, Abdul Wahab; Sahi, Nirmala; Nuna, Muten (Public Policy Journal, 2025)
Sustainable fisheries management in coastal areas is a challenge as wellas a strategic opportunity in maintaining the sustainability of marine resourcesand the welfare of fishing communities. Bone Bolango Regency, which has quitelarge fisheries potential, especially in the Tomini Bay area, faces variouschallenges in its fisheries governance, ranging from low community participation,limited responsive policy support, to minimal cross-sector collaboration. Thisstudy aims to analyze sustainable fisheries management in Bone Bolango byemphasizing the role of fishing communities, government responsiveness, andmulti-party partnerships. The method used in this study is a descriptivequalitative approach with data collection techniques through in-depthinterviews, field observations, and documentation studies. Data were analyzedusing the Business Model Canvas framework adapted to the Design Thinkingapproach to understand the dynamics of user needs, actor roles, and innovationin governance. The results of the study show that active participation of fishingcommunities has a significant influence on the legitimacy of policies and thesuccess of marine conservation programs based on local wisdom. However, thisinvolvement is still hampered by low environmental literacy and technicalcapacity. In addition, the level of responsiveness of local governments is stillpartial, focusing more on technical assistance than building equal dialoguemechanisms. Meanwhile, collaborative practices between fishing communities,government, and the private sector have not been optimal due to the weaknessof existing partnership institutions. This finding strengthens the arguments of anumber of previous studies that emphasize the importance of environmentaleducation, integration of local knowledge, and inclusive partnerships in coastalresource management. The implications of this study indicate that the success ofsustainable fisheries management is largely determined by an adaptive,community-based governance model supported by strategic cross-sectorpartnerships. Therefore, it is necessary to design policies and programs that aremore responsive to the needs of coastal communities, strengthen communitycapacity, and build participatory and sustainable collaborative institutions.